A facile and rapid access to resveratrol derivatives and their radioprotective activity. Issue 16 (15th August 2016) - Uzura, Saori; Sekine-Suzuki, Emiko; Nakanishi, Ikuo; Sonoda, Motohiro; Tanimori, Shinji
Graphical abstract: Abstract: A facile and rapid access to resveratrol derivatives has been achieved based on palladium-catalyzed oxidative Heck reaction of aryl boronic acids with styrenes followed by demethylation in moderate to good yields. A series of resveratrol derivatives with various functional groups has been synthesized easily. The radioprotective activity of synthesized compounds has also been evaluated using rat thymocytes. The results revealed that some resveratrol derivatives efficiently protected the thymocytes from radiation-induced apoptosis.